Cytochrome P450 inhibition potential of new psychoactive substances of the tryptamine class. (22nd January 2016) - Dinger, Julia; Woods, Campbell; Brandt, Simon D.; Meyer, Markus R.; Maurer, Hans H.
Highlights: All tested tryptamines inhibited at least one isoenzyme. IC50 values were comparable to that of clinically relevant inhibitors. Members of the DALT family were strong inhibitors of CYP1A2 and CYP2D6 activity. 5-MeO-DALT showed in vivo inhibition against CYP1A2 activity. Abstract: New psychoactive substances (NPS) are not tested for their cytochrome P450 (CYP) inhibition potential before consumption. Therefore, this potential was explored for tryptamine-derived NPS (TDNPS) including alpha-methyl tryptamines (AMTs), dimethyl tryptamines (DMTs), diallyl tryptamines (DALTs), and diisopropyl tryptamines (DiPTs) using test substrates preferred by the Food and Drug Administration in a cocktail assay. All tested TDNPS with the exception of DMT inhibited CYP2D6 activity with IC50 values below 100 μM. DALTs inhibited CYP2D6 activity similar to paroxetine and quinidine and CYP1A2 activity comparable to fluvoxamine. 5-Methoxy- N, N -diallyltryptamine reduced in vivo the caffeine metabolism in rats consistent with in vitro results. Five of the AMTs also inhibited CYP1A2 activity comparable to amiodarone. AMT and 6-F-AMT inhibited CYP2A6 activity in the range of the test inhibitor tranylcypromine. CYP2B6 activity was inhibited by 19 tryptamines, but weakly compared to efavirenz. CYP2C8 activity was inhibited by five of the tested TDNPS and three showed values comparable to trimethoprim and gemfibrozil. Six tryptamines inhibited CYP2C9 and seven CYP2C19 activities comparable to fluconazole and chloramphenicol, respectively. Nineteen compounds showed inhibition of CYP2E1 and 18 of CYP3A activity, respectively. These results showed that the CYP inhibition by TDNPS might be clinically relevant, but clinical studies are needed to explore this further.